Jardiner l’architecture émotionnelle - Nicolas Gilsoul (Projets de Paysage)
What would happen if we dream of gardening the architecture instead of designing our garden ? Which challenge would we face by planning with the gardener empiricism ? The article defines first of all the emotional architecture. It then analyses the key role of the empiricism in the method of conception and realization in emotional architecture based on Luis Barragán process experimented in Mexico between 1940 and 1980. The presentation is based on the architect, his collaborators and contractors testimonies and on historical documents which give an overview of the evolution of fragments of certain mise-en-scène. As an opening conclusion, the article questions the potential heritage of the emotional architecture, depending on its method, as soon as certain landscapers try to transform men in global gardener.